Malay Language as the Foundation of National Identity in the Selected Poetry Publications of Dewan Bahasa dan Pustaka: (Bahasa Melayu sebagai Teras Jati Diri Kebangsaan dalam Sajak Pilihan Terbitan Dewan Bahasa dan Pustaka) (Malay Literature, 2018)
The aim of this study is to analyse the theme of national identity in the poetry publications of Dewan Bahasa dan Pustaka (DBP). National identity is an important element in nation building. The government has emphasized on national identity and national unity as the foundation for creating a Malaysian nation with a strong national identity since the 13th May 1969 incident. This analysis uses the principles of the National Cultural Policy (formulated in 1971) as the conceptual framework, with focus on the Malay language as the foundation for a national identity. For this study, the content of the selected poetry published by DBP between 2010 and 2015 were analysed. The findings show that the poetry publications studied acknowledge the Malay language as the foundation for national identity.Keywords: national identity, National Cultural Policy; Dewan Bahasa dan Pustaka, selected poems